All in the Family : State Capture in Tunisia - Rijkers, Bob (World Bank, Washington, DC, 2014)
This paper examines the relationship between regulation and the business interests of President Ben Ali and his family, using firm-level data from Tunisia for 1994-2010. Data on investment regulations are merged with balance sheet and firm-level census data in which 220 firms owned by the Ben Ali family are identified. These connected firms outperform their competitors in terms of employment, output, market share, profits, and growth and sectors in which they are active are disproportionately subject to authorization requirements and restriction on foreign direct investment. Consistent with theories of capture, performance differences between connected firms and their peers are significantly larger in highly regulated sectors. In addition, the introduction of new foreign direct investment restrictions and authorization requirements in narrowly defined five-digit sectors is correlated with the presence of connected firms and with their startup, suggesting that regulation is endogenous to state capture. The evidence implies that Tunisia's industrial policy was used as a vehicle for rent creation for the president and his family.